Application of the audio-lingual method through a system of classes to develop vocabulary in english - Abad Conde, Yaritza Anabel; Robles Barragán, Rut Noemi (Machala: Universidad Técnica de Machala, 2024)
The research focused on improving the English vocabulary of seventh grade students through the implementation of the audio-lingual method. The study, framed in a quantitative and experimental approach, sought to determine the effectiveness of this method in the development of students’ linguistic skills. The research was based on a theoretical review that include a historical and conceptual analysis of the audio-lingual method, as well as relevant theories on vocabulary acquisition. The methodology employed combine theoretical hypothetical-deductive and analytic-synthetic and empirical participant observation and questionnaires methods. The results of the study showed a significant improvement in both active and passive vocabulary of the students after the pedagogical intervention based on the audio-lingual method. When comparing the results of the pre-test and post-test, and improvement the lexical knowledge of the participants was evidenced this research demonstrated that the implementation of audio-lingual method is an effective strategy to develop English vocabulary in elementary school students. The results obtained support the idea that this method, characterized by repetitive oral practice and language immersion, contributes significantly to vocabulary acquisition. The study demonstrates that the audio-lingual method is a valuable tool for improving the linguistic skills of English language learning, specifically with regard to vocabulary development.
La investigación se centró en mejorar el vocabulario en inglés de estudiantes de séptimo grado a través de la implementación del método audio lingual. El estudio, enmarcado en un enfoque cuantitativo y experimental, buscó determinar la efectividad de este método en el desarrollo de las habilidades lingüísticas de los estudiantes. Para fundamentar la investigación, se realizó una revisión teórica que incluyó un análisis histórico y conceptual del método audiolingual, así como de teorías relevantes sobre la adquisición de vocabulario. La metodología empleada combinó métodos teóricos hipotético-deductivo y analítico-sintético y empíricos observación participante y cuestionarios. Los resultados del estudio mostraron una mejora significativa en el vocabulario tanto activo como pasivo de los estudiantes después de la intervención pedagógica basada en el método audio-lingual. Al comparar los resultados del pre test y pot-test, se evidenció un avance en el conocimiento léxico de los participantes. Esta investigación demostró que la implementación del método audio-lingual es una estrategia efectiva para desarrollar el vocabulario en inglés en estudiantes de educación básica. Los resultados obtenidos respaldan la idea de que el método, caracterizado por la práctica oral repetitiva y la inmersión en el idioma, contribuye significativamente a la adquisición del vocabulario. El estudio demuestra que el método audio lingual es una herramienta valiosa para mejorar las habilidades lingüísticas de los estudiantes de inglés, específicamente en lo que respecta al desarrollo del vocabulario.
Keywords: AUDIO-LINGUAL METHOD; SYSTEM OF CLASSES; ACTIVE AND PASSIVE VOCABULARY; TEACHING-LEARNING PROCESS